2022
DOI: 10.1039/d2ew00653g
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale aerobic granular sludge for municipal wastewater treatment – granule formation, microbial succession, and process performance

Abstract: Aerobic granular sludge (AGS) plants have gained growing interest and application due to their low energy demand, small footprint, and low operational costs. However, the fulfilment of strict discharge limits...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
(123 reference statements)
2
15
0
Order By: Relevance
“…In the same subject, Sarma et al [21] underlined that there is a shortage of understanding of the precise factors that directly correlate with granules' size distribution and their microbial compositions. Ekholm et al [22] stated that the assembling mechanism of granules microbial communities is still undefined. Ekholm et al [22] and Hamiruddin et al [23] observed that the composition of microbial cultures is influenced by seasonal variations and wastewater characteristics.…”
Section: Operation Modes Of Granular Sludge Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same subject, Sarma et al [21] underlined that there is a shortage of understanding of the precise factors that directly correlate with granules' size distribution and their microbial compositions. Ekholm et al [22] stated that the assembling mechanism of granules microbial communities is still undefined. Ekholm et al [22] and Hamiruddin et al [23] observed that the composition of microbial cultures is influenced by seasonal variations and wastewater characteristics.…”
Section: Operation Modes Of Granular Sludge Unitsmentioning
confidence: 99%
“…Ekholm et al [22] stated that the assembling mechanism of granules microbial communities is still undefined. Ekholm et al [22] and Hamiruddin et al [23] observed that the composition of microbial cultures is influenced by seasonal variations and wastewater characteristics. In terms of operation mode, no clear observations reflect significant differences in the microbial clusters of cultivated granules from both SBR and CFR units [23,6].…”
Section: Operation Modes Of Granular Sludge Unitsmentioning
confidence: 99%
“…The AGS system comprised sequencing batch reactors whereas the CAS system was based on tanks in series with continuous flow. The case study was performed at the Österröd WWTP (Sweden), characterized by large fluctuations in nutrient loads and temperature (Ekholm et al, 2022). Effluent quality, land footprint, energy usage, and sludge production were compared for the two techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Biological nitrogen and phosphorus removal rely on the availability of organic substrates (Henze et al, 2019). The Dutch AGS plant had relatively high concentrations of organic matter in the influent (average concentrations of chemical oxygen demand [COD] 506 mg L −1 , biological oxygen demand [BOD] of 224 BOD 5 mg L −1 , and BOD/N‐ratio of 4.5), compared to the full‐scale AGS plant in Sweden (average concentrations of COD 277 mg L −1 , BOD 7 110 mg L −1 and BOD/N‐ratio of 3.2; Ekholm et al, 2022), which influences the process performance.…”
Section: Introductionmentioning
confidence: 99%
“…4 The immobilized microorganism technology and aerobic granulation technology could improve the sludge holding capacity of the reactor and cultivate the functional bacteria very quickly. 5,6 Moreover, it is powerful in enhancing the adaptability of sensitive bacteria to adverse environments by the protection of immobilized materials. 7 In recent years, the immobilized microorganism technology is a research hotspot in the treatment of biological sewage.…”
Section: Introductionmentioning
confidence: 99%